Behavior of concrete-filled T-shaped steel tubular beam-columns under biaxial compressive loads. (15th February 2023) - Lei, Min; Li, Ying-Lei; Li, Yuan-Qi; Zhang, Jicheng; Liu, Dewen
Highlights: Test on full-scale slender concrete-filled T -shaped steel tubular (CFTST) beam-columns under biaxial eccentric compression. Change of neutral axis position and orientation during the loading process of CFTSTs. Effects of axial force ratio, material property, cross-section dimension, and slenderness ratio on the interaction curves of beam-columns. New design method for CFTST beam-columns under biaxial eccentric compression. Abstract: Concrete-filled T-shaped steel tubular (CFTST) columns have a wide prospect of being used in high-rise buildings to avoid having protruding portions in walls. This paper presents an experimental and theoretical study on CFTST beam-columns under biaxial compressive loads. Five full-scale CFTSTs, including an axially loaded column and four biaxially loaded beam-columns, were tested and the failure modes, lateral deflections and strains were discussed. Current design methods originally for rectangular CFSTs offered a much conservative prediction for the tested T-shaped specimens as the cross-section is single-symmetric. Based on fiber element analysis, parametric study was conducted to investigate the effects of key parameters on the interaction curves that were normalized by the moment capacity of the specimen under uniaxial eccentric compression. Concrete strength, steel yield stress and steel tube thickness have insignificant effects on the normalized interaction curves but the influences of axial force ratio, cross-section dimensions and slenderness ratio are obvious. Finally, empirical interaction formulas in both complex and simplified forms were proposed for CFTSTs under biaxial eccentric loads. Accuracy of the proposed method was then verified by the experimental results and fiber element analysis results.